CREATIVE WORK AS A FACTOR OF EFFICIENCY GROWTH - Murat, Ikramov; Nigora, Abdurashidova (Prosiding Seminar SeNTIK, 2025)
The article examines the current problem of developing creative work in modern conditions. The author emphasizes the need to find new methods for achieving this, conducts a comparative analysis of the characteristics of mental and physical labor, proposes the "Honeybee Model" as a tool for activating creativity, and explores the impact of digitalization and the introduction of artificial intelligence on the development of creative competencies in economics students.